Detection of Theileria and Babesia species in sheep and goats by microscopy and molecular methods in Nigde province, Turkey - Karatepe, B.; Ozubek, S.; Karatepe, M.; Aktas, M. (Ecole Nationale Veterinaire Toulouse, 2019)
The present study was conducted to investigate presence and prevalence of Theileria and Babesia in sheep and goats of Nigde by microscopic and molecular methods. For this purpose, it was chosen a total of 690 small ruminants including 520 sheep and 170 goats between 1-10 year olds belonging to 28 flocks in Nigde province, in Central Anatolia of Turkey between April-July 2014. Blood smears were prepared from the blood samples, stained with Giemsa, and examined under the light microscope for Theileria and Babesia piroplasms. The piroplasm DNAs of Theileria and Babesia species was amplified using the RLB-F2 ve RLB-R2 primers. The polymerase chain reaction (PCR) products were hybridized to the membrane connected species-specific probes. The ticks were removed from sheep and goats and they were identified. Out of blood samples examined microscopically, 119 sheep (17.2%) were positive for Theileria spp. or Babesia spp., whereas no goats were positive. Of 690 animals 344 (49.8%) were positive for Theileria or Babesia by RLB method. Theileria ovis was the most common blood parasites in sheep and goats in the region with 46.9%, this is followed by B. ovis with 3.5% and Theileria sp. MK with 1.4%. The other Theileria species (T. lestoquardi, T. luwenshuni, T. uilenbergi) and genotypes (Theileria sp. OT1, Theileria sp. OT3) and Babesia species (B. motasi, B. crassa) were not detected in sheep and goats in the region. A total of 1361 ticks were collected in sheep and goats and they identified as Rhipicephalus bursa, R. turanicus, Hyalomma marginatum, Hy. excavatum, Hy. anatolicum, Haemophsalis parva, Hae. punctata, Hae. sulcata and Dermacentor marginatus. In determining blood parasites in sheep and goats, it was determined that PCR and RLB results were more susceptible than microscopy (P < 0.05,chi(2) = 105.823; P < 0.05,chi(2) = 164.548), and RLB than to PCR.
Keywords: Sheep; goat; Theileria; Babesia; tick; microscopy; RLB